Hydraulic properties for a wide range of undisturbed and compacted French forest soils: in situ measurements and estimation with the BEST method - Manon Martin; André Chanzy; Laurent Lassabatere; Arnaud Legout; Noémie Pousse; Stéphane Ruy (Annals of Forest Science)
Abstract Key message The dataset provides hydraulic properties estimated using the Beerkan Estimation of Soil Transfer (BEST) method, on undisturbed and on compacted and rutted French forest soils. It allows a reliable assessment of the effect of traffic on soil permeability. However, hydraulic properties could not be estimated on extremely rutted soils, underscoring the necessity for tailored protocols for these conditions.